2022
DOI: 10.3390/gases2010001
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Factors in Enhanced Coal Bed Methane Recovery: A Review

Abstract: Enhanced coal bed methane recovery using gas injection can provide increased methane extraction depending on the characteristics of the coal and the gas that is used. Accurate prediction of the extent of gas adsorption by coal are therefore important. Both experimental methods and modeling have been used to assess gas adsorption and its effects, including volumetric and gravimetric techniques, as well as the Ono–Kondo model and other numerical simulations. Thermodynamic parameters may be used to model adsorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 144 publications
0
6
0
Order By: Relevance
“…Coals with vitrinite are well cleated with a high surface specific area and thus are more permeable. Vitrinite affects coal pore structure, especially micropores and pore distribution. ,,, (10) High Langmuir volume and pressure are suitable in CO 2 -ECBM technology application for CO 2 sequestration and CH 4 recovery …”
Section: Reservoir Screening Criteria For Co2-ecbm Technology Applica...mentioning
confidence: 99%
“…Coals with vitrinite are well cleated with a high surface specific area and thus are more permeable. Vitrinite affects coal pore structure, especially micropores and pore distribution. ,,, (10) High Langmuir volume and pressure are suitable in CO 2 -ECBM technology application for CO 2 sequestration and CH 4 recovery …”
Section: Reservoir Screening Criteria For Co2-ecbm Technology Applica...mentioning
confidence: 99%
“…Methane produced is used as an energy source rather than releasing it into the atmosphere, which can defeat the purpose of sequestering CO2 as methane is 23 times more potent GHG than CO2 (Riley 2010). A study by Tambaria et al (2022) concluded that moisture, maceral and pore size and characteristics of injected gas are the three most important factor that determine the efficiency of the ECBMR process. Table 6 of Leung et al (2014) lists the ECBMR plants.…”
Section: B5 Enhanced Coal Bed Methane Recovery (Ecbmr)mentioning
confidence: 99%
“…Drying and crushing low-rank coal in Indonesia increase its CO 2 adsorption capacity, with drying having a more significant effect than crushing . Dry coal was also found to have a greater capacity for transporting gases and storing CO 2 than coal containing moisture, while coal with high moisture content had a lower gas adsorption capacity. The adsorption capacity of CO 2 is also influenced by other specific characteristics of coal, such as ash yield, maceral content, and coal pore effects. …”
Section: Introductionmentioning
confidence: 98%